Global incidence of primary malignant bone tumors. Issue 5 (September 2016) - Kumar, Narinder; Gupta, Bhawna
Abstract : Background: Though the incidence of primary malignant bone tumors is relatively low, the mortality related to them is disproportionately high, especially among teenagers and young adults. The currently available incidence figures are based mainly on data collected from more developed countries. Global incidence figures and comparative figures between various regions and continents are not available. Methods: The global incidence rates for primary malignant bone tumors across all age groups were estimated using the data from the Cancer Incidence in Five Continents, IARC CI5-annual detailed data set (ADDS). Comparison of incidence rates was done across all age groups and continents, including gender comparison. The data are presented in 5-year age brackets from birth until maximal possible age for which data were available in the database. Results: The global incidence of primary malignant bone tumors shows a specific age distribution pattern with two incidence peaks at 10-20 yr and a steady increase from 40 yr to the age of 80 yr. There is a significant difference between males and females, with males being affected almost 1.5 times more frequently than females. South America had the highest incidence rates in both the peak age groups affected. Conclusions: There are significant geographic variations in incidence of primary malignant bone tumors with variation being more significant in elderly age group.